2018
DOI: 10.3138/cjhs.2018-001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-climactic: Investigating how late adolescents perceive and deal with orgasm difficulty in the context of their intimate relationships

Abstract: There is a long history of survey research indicating high rates of orgasm difficulties among adults. We sought to investigate how male and female heterosexual late adolescents perceive difficulties with orgasm, whether gender differences were apparent, and how they tried to resolve these difficulties (if at all). We conducted semi-structured interviews with 53 heterosexual male and female adolescents, aged 18–21 years. Interviews were guided around the question of when sex was not as good as they thought it s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It is also possible that well-educated young women are particularly engaged in self-optimization, which may encourage sexual pressure to perform. Moreover, there is little education about sexual functioning at school (Cormier & O'Sullivan, 2018), which could be a possible reason for this pressure. It is especially important for adolescents to discover their own bodies: Regular masturbation during this time facilitates experiencing orgasms during sexual intercourse (Carvalheira & Leal, 2013).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…It is also possible that well-educated young women are particularly engaged in self-optimization, which may encourage sexual pressure to perform. Moreover, there is little education about sexual functioning at school (Cormier & O'Sullivan, 2018), which could be a possible reason for this pressure. It is especially important for adolescents to discover their own bodies: Regular masturbation during this time facilitates experiencing orgasms during sexual intercourse (Carvalheira & Leal, 2013).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…wanting access to more inclusive information that is practically While the importance of online and community-based pro-and culturally relevant, and includes positive messaging about gramming cannot be overstated, the literature suggests a sense of sex and relationships ( e.g., Causarano et al, 2010 ;Cormier & appreciation for receiving sexual health education at school. For O 'Sullivan, 2018 ;Larkin et al, 2017;Martinez & Phillips, 2008; example, a sample of high school students in New Brunswick re- Narushima et al, 2020 ;Flicker et al, 2009 ).…”
mentioning
confidence: 99%
“…Y outh in these Toronto-based studies (Causarano et al, 2010;Narushima et al, 2020) also expressed wanting to receive more positive messag es and learn more about sexual pleasure. In another Canadian study, Cormier and O'Sullivan (2018 ) observed that participants (ages 18-21) retrospectively felt dissatisfied that their sexual health education had skipped over sexual pleasure as a topic.…”
mentioning
confidence: 99%